What do globular clusters tell us about isolated ellipticals? The case of NGC 6411 - Caso, Juan Pablo (2020)
We summarize the results from a study of the globular cluster (GC) system of the isolated elliptical galaxy NGC 6411, based on Gemini/GMOS g´, r´, i´ photometry. The extent of the globular cluster system is about 70 kpc. It contains ≍700 members. The colour distribution and luminosity function are typical of old GC systems. An excess of bright GCs with intermediate colours might evidence an intermediate-age merger.